THE INFLUENCE OF INSTAGRAM PROMOTION AND SERVICE QUALITY ON THE PURCHASE DECISION OF BANANA PASIR WAIS THROUGH ONLINE OJEK - Dewi Andriany; Mutia Arda (RADJA PUBLIKA, 2023)
The purpose of this study was to find out whether promotion on Instagram and service quality simultaneously and partially had a positive and significant effect on the decision to purchase Pasir Wais bananas through online motorcycle taxis during the Covid-19 pandemic in the city of Medan. The F statistical test was carried out to test whether the independent variable (X) simultaneously has a significant relationship or not to the dependent variable (Y). Based on the statistical test results shown in the table above, the calculated F value is 45.309> F table 4.08 with a significance value of 0.000 which is less than 0.05. The significance value of Promotion (X1) is 0.001 <0.05 and the t count is 3.595 > t table 3.30127 indicating that Promotion (X1) has a significant effect on Purchase Decisions. So, the hypothesis of the influence of Promotion on Purchase Decision (H1) is accepted. The significance value of Service Quality (X2) is 0.000 <0.05 and the t count value is 4.575> t table 3.30127 indicating that Service Quality (X2) has an effect on Purchasing Decisions. Thus, the hypothesis of the effect of service quality on purchasing decisions (H2) is accepted. This indicates that partially service quality has a positive and significant effect on purchasing decisions of bananas and wais bananas through online motorcycle taxis.